2023
DOI: 10.1039/d2sc06044b
|View full text |Cite
|
Sign up to set email alerts
|

One-pot cascade construction of nonsubstituted quinoline-bridged covalent organic frameworks

Abstract: Irreversible locking of imine linkage into stable linkages represents a promising strategy to improve the robustness and functionality of covalent organic frameworks (COFs). We report, for the first time, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…In our previous study, it was reported that NQ-COFs linked by nonsubstituted quinoline exhibited a higher photogenerated efficiency of •O 2 – compared to the corresponding imine-linked COFs . In the present investigation, the ability of photogenerated •O 2 – by Am-COF D4 was evaluated using electron paramagnetic resonance (EPR) measurements (Figure f).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…In our previous study, it was reported that NQ-COFs linked by nonsubstituted quinoline exhibited a higher photogenerated efficiency of •O 2 – compared to the corresponding imine-linked COFs . In the present investigation, the ability of photogenerated •O 2 – by Am-COF D4 was evaluated using electron paramagnetic resonance (EPR) measurements (Figure f).…”
Section: Resultsmentioning
confidence: 75%
“…In the present investigation, the ability of photogenerated •O 2 – by Am-COF D4 was evaluated using electron paramagnetic resonance (EPR) measurements (Figure f). However, the weakest signals of •O 2 – adducts in the presence of 5,5-dimethyl-1-pyrroline N -oxide (DMPO) were observed, and then the inapplicability of Am-COF D4 to •O 2 – -mediated reactions was demonstrated by the photocatalytic synthesis of benzimidazoles . Subsequently, various types of photocatalytic organic transformations were evaluated, and the dehalogenation of α-bromoacetophenone derivatives, which is driven by the singlet electron transfer (SET), was selected for further investigation .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations